2000
DOI: 10.1037/0096-3445.129.4.427
|View full text |Cite
|
Sign up to set email alerts
|

Temporal context and conditioned reinforcement value.

Abstract: The effectiveness of a stimulus as a conditioned reinforcer depends on the temporal context of reinforcement, that is, the overall rate of reinforcement in the situation. The dominant view has been that context determines the learned value of a stimulus directly, according to delay-reduction theory. By contrast, the contextual choice model (CCM) maintains that value is independent of context and incorporates the effects of context on choice in the framework of the matching law. The authors report 2 experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
48
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(53 citation statements)
references
References 60 publications
(109 reference statements)
5
48
0
Order By: Relevance
“…If the value of a stimulus in a simultaneous discrimination is not enhanced by following a relatively effortful response requirement, the apparent discrepancy noted in the introduction between the work ethic effect in pigeons and the findings of Grace and Savastano (2000) is resolved. However, there is evidence that after training on multiplechain schedules, a preference does emerge for the terminallink stimulus that follows a longer initial link (O'Daly, Angulo, Gipson, & Fantino, 2006;O'Daly, Meyer, & Fantino, 2005).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…If the value of a stimulus in a simultaneous discrimination is not enhanced by following a relatively effortful response requirement, the apparent discrepancy noted in the introduction between the work ethic effect in pigeons and the findings of Grace and Savastano (2000) is resolved. However, there is evidence that after training on multiplechain schedules, a preference does emerge for the terminallink stimulus that follows a longer initial link (O'Daly, Angulo, Gipson, & Fantino, 2006;O'Daly, Meyer, & Fantino, 2005).…”
Section: Discussionmentioning
confidence: 98%
“…The advantage of random, nondifferential reinforcement is that responding can be maintained indefinitely over multiple test sessions, as compared with probe trials that always end in nonreinforcement (cf. Grace & Savastano, 2000). There is no reason to expect that such reinforcement would bias responding one way or the other, so any preferences found can be interpreted as baseline transfer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They also suggested, instead, that the relative value of the two VI 40-sec components would be better assessed by arranging them as terminal links in concurrent chains to test the relative reinforcing strength in a manner used by Grace and Savastano (1997). Although that initial study produced ambiguous results, a subsequent study by Grace and Savastano (2000) has shown clearly that preference assessed in probe trials after training in concurrent chains is controlled by the absolute value of the terminal link schedules, regardless of the level of initiallink preference associated with them. For example, in Experiment 1 of their study, the initial-link schedules during Component A were VI 15-sec versus VI 15-sec with terminal links of VI 10-sec versus VI 20-sec; during Component B, the initial-linkschedules were VI 30-sec versus VI 30-sec, with terminal links of VI 20-sec versus VI 40-sec.…”
Section: Discussionmentioning
confidence: 99%